The habenular volume and PDE7A allelic polymorphism in major depressive disorder: preliminary findings. (16th March 2023) - Aftanas, Lyubomir I.; Filimonova, Elena A.; Anisimenko, Maksim S.; Berdyugina, Darya A.; Rezakova, Maria V.; Simutkin, German G.; Bokhan, Nikolay A.; Ivanova, Svetlana A.; Danilenko, Konstantin V.; Lipina, Tatiana V.
Abstract: Objectives: The habenula is a brain structure implicated in depression, yet with unknown molecular mechanisms. Several phosphodiesterases (PDEs) have been associated with a risk of depression. Although the role of PDE7A in the brain is unknown, it has enriched expression in the medial habenula, suggesting that it may play a role in depression. Methods: We analysed: (1) habenula volume assessed by 3-T magnetic resonance imaging (MRI) in 84 patients with major depressive disorder (MDD) and 41 healthy controls; (2) frequencies of 10 single nucleotide polymorphisms (SNPs) in PDE7A gene in 235 patients and 41 controls; and (3) both indices in 80 patients and 27 controls. The analyses considered gender, age, body mass index and season of the MRI examination. Results: The analysis did not reveal habenula volumetric changes in MDD patients regardless of PDE7A SNPs. However, in the combined group, the carriers of one or more mutations among 10 SNPs in the PDE7A gene had a lower volume of the left habenula (driven mainly by rs972362 and rs138599850 mutations) and consequently had the reduced habenular laterality index in comparison with individuals without PDE7A mutations. Conclusions: Our findings suggest the implication of the PDE7A gene into mechanisms determining the habenula structure.